Metode Arch/Garch untuk memprediksi hubungan Economic Uncertainty akibat Pandemi Covid 19 dan Volatilitas Saham - Sumiyati Sumiyati; Boy Dian Anugra Sandy; Panggio Restu Wilujeng (Jurnal Bisnis dan Akuntansi, 2022)
The capital markets of the United States and Indonesia experienced stock market crashes in which stock prices fell sharply and several stock indexes were forced to close prematurely. This study aims to determine the effect of economic uncertainty on the market reaction when the COVID-19 outbreak hit Indonesia. This research is a quantitative research with an event study approach. The time period starts from February to March 2020. The data is time series obtained from www.policyuncertainty.com to calculate the Economic Policy Uncertainty (EPU) Index as a measure of the economic uncertainty variable. Meanwhile, stock returns used the closing stock prices of JCI from February to March 2020 to measure volatility. The data were processed using the Unit Root Test- Augmented Dickey-Fuller to test the stationary and the ARCH/GARCH method to test the effect of the variable. The results show that EPU has no effect on stock volatility in Indonesia in the short term, but has an effect in the long term. This research contributes to the development of the event study literature in the behavior of investors in the capital market as a result of unpredictable events. As well as responses to policies formulated by stakeholders to address future economic uncertainties..